A positive feedback loop between STAT3 and cyclooxygenase‐2 gene may contribute to Helicobacter pylori‐associated human gastric tumorigenesis. Issue 9 (1st November 2013) - Xiong, Hua; Du, Wan; Sun, Tian‐Tian; Lin, Yan‐Wei; Wang, Ji‐Lin; Hong, Jie; Fang, Jing‐Yuan
<x xml:space="preserve">Abstract</x> Persistent infection with Helicobacter pylori (H. pylori) contributes to gastric diseases including chronic gastritis and gastric cancer. However, the pathogenesis of this carcinogenic bacterium has not been completely elucidated. Here, we report that H. pylori rapidly triggers STAT3 signaling and induces STAT3‐dependent COX‐2 expression both in vitro and in vivo. STAT3 upregulats COX‐2 by binding to and increasing the activity of COX‐2 promoter. COX‐2 in turn regulates IL‐6/STAT3 signaling under basal conditions and during H. pylori infection. These findings suggest that a positive feedback loop between STAT3 and COX‐2 exists in the basal condition and H. pylori infectious condition. Immunohistochemical staining revealed that H. pylori‐positive gastritis tissues exhibited markedly higher levels of pSTAT3Tyr705 than H. pylori‐negative ones. High pSTAT3Tyr705 levels are correlated with intestinal metaplasia and dysplasia, suggesting pSTAT3Tyr705 may be useful in the early detection of gastric tumorigenesis. Additionally, a strong positive correlation between STAT3/pSTAT3Tyr705 levels and COX‐2 expression was identified in gastritis and gastric cancer tissues. Together, these findings provide new evidence for a positive feedback loop between STAT3 signaling and COX‐2 in H. pylori pathogenesis and may lead to new approaches for early detection and effective therapy of gastric cancer.